Engineered skeletal muscles for disease modeling and drug discovery. (November 2019) - Wang, Jason; Khodabukus, Alastair; Rao, Lingjun; Vandusen, Keith; Abutaleb, Nadia; Bursac, Nenad
Abstract: Skeletal muscle is the largest organ of human body with several important roles in everyday movement and metabolic homeostasis. The limited ability of small animal models of muscle disease to accurately predict drug efficacy and toxicity in humans has prompted the development in vitro models of human skeletal muscle that fatefully recapitulate cell and tissue level functions and drug responses. We first review methods for development of three-dimensional engineered muscle tissues and organ-on-a-chip microphysiological systems and discuss their potential utility in drug discovery research and development of new regenerative therapies. Furthermore, we describe strategies to increase the functional maturation of engineered muscle, and motivate the importance of incorporating multiple tissue types on the same chip to model organ cross-talk and generate more predictive drug development platforms. Finally, we review the ability of available in vitro systems to model diseases such as type II diabetes, Duchenne muscular dystrophy, Pompe disease, and dysferlinopathy. Graphical abstract: In vitro models of human skeletal muscle. Human pluripotent stem cells (hPSCs) are differentiated to the myogenic fate through overexpression of transgenes, such as MyoD or Pax7, or transgene-free protocols, while primary muscle stem cells are dissociated from muscle biopsies and expanded in vitro . Additional cell types (endothelial cells, motor neurons, and macrophages) can be added to mimic the cellular heterogeneity of native muscle. Various muscle-resident cells are compartmentalized in microfluidic devices (muscle-on-a-chip) or co-cultured in 3D engineered tissues that permit non-destructive longitudinal testing of changes in muscle contractile and metabolic function in response to various drugs, injuries, exercise-mimetic stimulation, and crosstalk with other organ-on-chip (OOC) models.Image 1